2015
DOI: 10.1007/s13593-015-0338-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulated deficit irrigation for crop production under drought stress. A review

Abstract: Agriculture consumes more than two thirds of the total freshwater of the planet. This issue causes substantial conflict in freshwater allocation between agriculture and other economic sectors. Regulated deficit irrigation (RDI) is key technology because it helps to improve water use efficiency. Nonetheless, there is a lack of understanding of the mechanisms with which plants respond to RDI. In particular, little is known about how RDI might increase crop production while reducing the amount of irrigation water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
279
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(299 citation statements)
references
References 138 publications
(188 reference statements)
6
279
2
12
Order By: Relevance
“…In our study, the water saving in direct-seeded rice was not so evident because the plots were kept under flooded conditions soon after crop establishment. Some water management practices could be adopted to further save the water input and increase water productivity in directseeded rice, such as rainfed (Zhao et al 2007), alternate wet and dry (Bouman and Tuong 2001), regulated deficit irrigation (Chai et al 2016). Yoshida (1981) reported that 1240 mm was an average water requirement to produce a reasonably good crop of rice.…”
Section: Ch 4 and N 2 O Emissions And Global Warming Potentialmentioning
confidence: 99%
“…In our study, the water saving in direct-seeded rice was not so evident because the plots were kept under flooded conditions soon after crop establishment. Some water management practices could be adopted to further save the water input and increase water productivity in directseeded rice, such as rainfed (Zhao et al 2007), alternate wet and dry (Bouman and Tuong 2001), regulated deficit irrigation (Chai et al 2016). Yoshida (1981) reported that 1240 mm was an average water requirement to produce a reasonably good crop of rice.…”
Section: Ch 4 and N 2 O Emissions And Global Warming Potentialmentioning
confidence: 99%
“…It is important to point out that stem water potential values, measured at midday during the three seasons in the present study, were higher than the threshold proposed by Van Leeuwen et al (2009) Water stress was not found in the present study, not even in the treatment without irrigation. This situation would indicate permanent and effective activity of the vine plants' deep root systems, and that the presence of a shallow water table would permit root water uptake as sub-surface irrigation (Chai et al, 2016). The presence of a shallow water table in Chile has only been described by Fredes et al (2010) for 'Carménère' grapevines (phreatic level depth at 2 m), but this background information has not been considered in most authors' reports.…”
Section: Matric Potential and Midday Stem Water Potential Of Vineyardmentioning
confidence: 99%
“…For explaining the physiological and biochemical background of deficit irrigation methods, including PRD technique, several review papers could be recommended (Costa et al, 2007;Fereres and Soriano, 2007;Ruiz-Sanchez et al, 2010;Sepaskhah and Ahmadi, 2010;Stikić et al, 2010;Du et al, 2015;Chai et al, 2016;Galindo et al, 2017;Kang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%